2014
DOI: 10.1016/j.virol.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of host extracellular signal-regulated kinase (ERK) activation decreases new world alphavirus multiplication in infected cells

Abstract: New World alphaviruses belonging to the family Togaviridae are classified as emerging infectious agents and Category B select agents. Our study is focused on the role of the host extracellular signal-regulated kinase (ERK) in the infectious process of New World alphaviruses. Infection of human cells by Venezuelan equine encephalitis virus (VEEV) results in the activation of the ERK-signaling cascade. Inhibition of ERK1/2 by the small molecule inhibitor Ag-126 results in inhibition of viral multiplication. Ag-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…We have previously demonstrated that VEEV infection leads to robust activation of the MEK/ERK signaling cascade, which is important for the virus to establish a productive infection. 7 In the case of HCV infected cells, similar clustering of mitochondria was demonstrated. 59 In HIV infected cells, mitochondria displayed morphological alterations including disappearance of cristae.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We have previously demonstrated that VEEV infection leads to robust activation of the MEK/ERK signaling cascade, which is important for the virus to establish a productive infection. 7 In the case of HCV infected cells, similar clustering of mitochondria was demonstrated. 59 In HIV infected cells, mitochondria displayed morphological alterations including disappearance of cristae.…”
Section: Discussionmentioning
confidence: 69%
“…We utilized the TC-83 virus to study the consequences of infection on astrocytoma cells (U87MG cells), as we have demonstrated in the past that TC-83 infection induces several innate immune signaling events and leads to death of infected cells. 6,7 Cumulatively, our studies indicate that VEEV infection disrupts mitochondrial structure and function. We demonstrate that mitochondrial fission may partially contribute to apoptosis that occurs in infected cells.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is to our knowledge the first experimental evidence of all major MAPK signaling pathways being concomitantly activated in the course of CHIKV infection in human cells. The induction of the Ras-Raf-MEK-ERK pathway has been shown for different RNA viruses like hepatitis C virus (53) and dengue virus (54) and also alphaviruses, namely, Sindbis virus (SINV) (20) and Venezuelan equine encephalitis virus (VEEV) (55). This pathway appears to be activated by these different viruses, potentially to confer a prosurvival status to the infected cells in order to maintain a productive infection cycle and generate sufficient progeny virions.…”
Section: Discussionmentioning
confidence: 99%